Study of the Molecular Structure, Spectroscopic Analysis, Electronic Structures and Thermodynamic Properties of Niacin Molecule Using First-principles - Budha, Chandra; Rai, Krishna Bahadur (Journal of Nepal Chemical Society, 2024)
This work describes the different properties of Niacin's molecule using the density functional theory (DFT) B3LYP/6-311++G (d, p) basis set. The optimized energy for the Niacin molecule is -436.987 Hartree. The peak values from FT-IR spectra show the C=C, C-C vibrations, C-H stretching vibrations, C-H in-plane bending vibration, C-H out-of-plane bending vibration, C-O stretching vibration, C-N vibration and O-H vibration. The MEP and ESP analyses indicate that the oxygen and nitrogen atoms exhibit nucleophilic regions, while the hydrogen atoms exhibit electrophilic regions. The energy gap of the Niacin molecule is found to be 5.398 eV through HOMO-LUMO analysis. The electronegativity value of 4.847 eV signifies the molecules ability to attract electron and the calculated value of chemical hardness is 2.7 eV which reflects the molecular stability. The softness value of 0.370 eV-1 denotes the molecule polarizability. Also the chemical potential value is -4.847 eV which represent the ability to donate or accept electron. Similarly, electrophilic index with value 4.351 eV shows the electrophilic behavior that signifies its capacity to accept electron. Because of the larger energy gap, the molecule becomes hard and hardness is greater than softness. In this molecule, the C2 atoms have the highest positive charge along with C3 and all the hydrogen atoms, while C1 has the highest negative charge together with some negative charge on C4, C5, N6, C11, O12 and O13 atoms. When the temperature rises, the thermodynamic parameters such as heat capacity at constant volume and pressure, internal energy, enthalpy, and entropy increase, but Gibbs free energy decreases.